Enlightened religion: from confessional churches to polite piety in the Dutch Republic - Spaans, Joke; Touber, Jetze (Brill's studies in intellectual history, 2019)
The history of the relation between religion and Enlightenment has been virtually rewritten In recent decades. The idea of a fairly unidirectional 'rise of paganism', or 'secularisation', has been replaced by a much more variegated panorama of interlocking changes-not least in the nature of both religion and rationalism. This volume explores developments in various cultural fields-from lexicology to geographical exploration, and from philosophy and history to theology, media and the arts-involved in the transformation of worldviews in the decades around 1700. The main focus is on the Dutch Republic, where discussion culture was more inclusive than in most other countries, and where people from very different walks of life joined the conversation. Contributors include: Wiep van Bunge, Frank Daudeij, Martin Gierl, Albert Gootjes, Trudelien van 't Hof, Jonathan Israel, Henri Krop, Fred van Lieburg, Jaap Nieuwstraten, Joke Spaans, Jetze Touber, and Arthur Weststeijn